Characterisation of the effects of pulsed radio frequency treatment of the dorsal root ganglion on cerebrospinal fluid cellular and peptide constituents in patients with chronic radicular pain: a randomised, triple-blinded controlled trial - Conroy, Melissa (My University, 2020)
Introduction: Chronic radicular neuropathic pain is a major clinical problem with a life time prevalence of more than 50%. Pulsed radiofrequency (PRF) treatment is a recognised therapy. However, the pathophysiology of chronic neuropathic pain (CNP) and the mechanism of action of PRF remains ill-defined. Improving our knowledge of the mechanisms of CNP and PRF action will enhance our ability to treat patients with this common debilitating problem more effectively. This study aims to characterise the CSF cellular and peptide constituents in patients with CNP and the effect of pulsed radiofrequency (PRF) on these constituents and reported pain. Materials and methods: Prospective randomised tripled-blinded control trial of patients receiving PRF treatment versus sham for radicular pain. All patients received local anaesthetic to the appropriate dermatome to confirm diagnosis. Clinical assessment using standard clinical assessment tools and examination of CSF using flow cytometry and ELISA for cellular and peptide constituents was carried out before and 3 months after treatment. Results: Ten patients were randomised to PRF (n = 5) or Sham (n = 5) treatment. PRF resulted in a significant reduction in pain score (NRS) at 3 months (6.8 to 2.6, p < .05). PRF reduced the TNF-α concentration and CD3+ count in CSF. CD4/CD8 ratio of patients with CNP was lower than historical controls (1.4 versus 3.0-4.2). The majority of CD3+ cells in the CNP patients were activated effector memory cells (80%) versus the surveillance central memory cells (85%) seen in healthy controls. Conclusions: PRF is superior to local anaesthetic administration for the management of radicular pain and is associated with CSF constituent modulation in vivo. Patients with CNP have lymphocyte characteristics which suggest immune activation.
PUBLISHED
Keywords: Cerebrospinal fluid; Dorsal root ganglion; Lymphocyte; Neuropeptide; Pulsed radiofrequency; Radicular pain; Immunology, Inflammation & Infection; Neuroscience; Chronic inflamation; Immune system; Medical Sciences, Research; Medicine